RELEVANSI KOMPONEN KURIKULUM PAI DENGAN KEBUTUHAN PEMBELAJARAN ABAD 21 - Nur Rohfitta; Agus Pahrudin; Agus Jatmiko; Koderi; Imam Syafe’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The 21st century is characterized by rapid technological advancement, globalization, and complex social dynamics, demanding that education systems adapt quickly and remain relevant to these changes. In this context, the Islamic Religious Education (PAI) curriculum holds a strategic role in shaping students’ character, spirituality, and competencies to face global challenges while maintaining Islamic identity. This study aims to analyze the relevance of the components of the PAI curriculum including objectives, content, learning strategies, and evaluation with the needs of 21st-century learning. The research employed a library research method by reviewing various academic sources, books, and studies published between 2015 and 2025. Data were analyzed qualitatively and descriptively through interpretation of theoretical findings related to the integration of Islamic values and 21st-century skills. The results indicate that the PAI curriculum should be developed adaptively and contextually by integrating critical thinking, creativity, collaboration, communication, and digital literacy into its core components. Moreover, PAI learning should emphasize active, collaborative, and project-based approaches accompanied by authentic assessment that holistically measures cognitive, affective, and psychomotor aspects. Strengthening spiritual, social, and moral values serves as a crucial foundation so that Islamic education does not merely transfer knowledge but also builds character and essential 21st-century competencies. Therefore, developing a relevant and sustainable PAI curriculum becomes a strategic effort to cultivate a generation of Muslims who are religious, morally upright, digitally literate, and capable of contributing positively to global civilization.